Neuronal-specific impairment of heparan sulfate degradation in Drosophila reveals pathogenic mechanisms for Mucopolysaccharidosis type IIIA. - Webber, D.L.; Choo, A.; Hewson, L.J.; Trim, P.J.; Snel, M.F.; Hopwood, J.J.; Richards, R.I.; Hemsley, K.M.; O'Keefe, L.V. (Experimental Neurology, 2018)
Mucopolysaccharidosis type IIIA (MPS IIIA) is a lysosomal storage disorder resulting from the deficit of the N-sulfoglucosamine sulfohydrolase (SGSH) enzyme that leads to accumulation of partially-degraded heparan sulfate. MPS IIIA is characterized by severe neurological symptoms, clinically presenting as Sanfilippo syndrome, for which no effective therapy is available. The lysosomal SGSH enzyme is conserved in Drosophila and we have identified increased levels of heparan sulfate in flies with ubiquitous knockdown of SGSH/CG14291. Using neuronal specific knockdown of SGSH/CG14291 we have also observed a higher abundance of Lysotracker-positive puncta as well as increased expression of GFP tagged Ref(2)P supporting disruption to lysosomal function. We have also observed a progressive defect in climbing ability, a hallmark of neurological dysfunction. Genetic screens indicate proteins and pathways that can functionally modify the climbing phenotype, including autophagy-related proteins (Atg1 and Atg18), superoxide dismutase enzymes (Sod1 and Sod2) and heat shock protein (HSPA1). In addition, reducing heparan sulfate biosynthesis by knocking down sulfateless or slalom expression significantly worsens the phenotype; an important observation given that substrate inhibition is being evaluated clinically as a treatment for MPS IIIA. Identifying the cellular pathways that can modify MPS IIIA neuropathology is an essential step in the development of novel therapeutic approaches to prevent and/or ameliorate symptoms in children with Sanfilippo syndrome.